Parasitic substrate coupling in high voltage integrated circuits : minority and majority carriers propagation in semiconductor substrate /: minority and majority carriers propagation in semiconductor substrate. (2018) - Buccella, Pietro; Stefanucci, Camillo; Kayal, Maher; Sallese, Jean-Michel
No abstract available